2015
DOI: 10.4236/oju.2015.52002
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Urinary Lithiasis: Epidemiology and Management at Urology Department of University Hospital of Cotonou

Abstract: Purpose: To study the epidemiology and treatment modalities of urolithiasis at Urology Department of University Hospital of Cotonou. Materials and Methods: It was a retrospective and descriptive study over a 10 years period ranging from January 1st, 2004 to December 31st, 2013. One hundred and two patients who were hospitalized for symptomatic urolithiasis at the Urology Department of University Hospital of Cotonou were enrolled. Results: Hospital incidence of urolithiasis was 3.7%. Patients mean age was 39.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…This holds true in reports from our country and elsewhere. 2,5,9,11,13,16,25,29 In contrast to this, studies from USA, Japan and Nigeria found out that calculi are frequent in the 5th and 6th decade of life. 1,12,32 This variation may be explained by a difference in study subjects and geographic location.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This holds true in reports from our country and elsewhere. 2,5,9,11,13,16,25,29 In contrast to this, studies from USA, Japan and Nigeria found out that calculi are frequent in the 5th and 6th decade of life. 1,12,32 This variation may be explained by a difference in study subjects and geographic location.…”
Section: Discussionmentioning
confidence: 93%
“…11,[25][26][27] Furthermore, reports from other countries recognized urolithiasis among the major reasons of urologic surgical admission. 2,3,14 Worldwide, the estimated male to female ratio of urolithiasis ranges from 1.5 to 2.5:1. 7 Comparable with this, our study and others also confirmed urolithiasis as a male predominant disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect is marked in higher income countries, but is attenuated in lower-middle income countries 8 10. This may be attributable to lack of availability of prompt intervention in developing countries, leading to later presentation and invasive treatments including nephrectomy 59–61. Following surgical treatment, management to prevent recurrence is recommended,13 again this may not be available in developing countries.…”
Section: Discussionmentioning
confidence: 99%